Die Bedeutung des Adler-Gleichnisses in Beethovens Brief an Therese Gräfin Brunswick: Ein Beitrag zu seiner Biographie - Tellenbach, Marie-Elisabeth (Die Musikforschung, 1999)
On November 23, 1810, Beethoven wrote to Therese Brunswick requesting a copy of a drawing showing an eagle looking into the sun: "So it was, I cannot forget." The widow Josephine had once exchanged love letters with Beethoven but was now married to Baron Stackelberg and unwilling to grant Beethoven's request. - Petrarch used the parable when referring to himself, the eagle, and Laura, the sun. J.M.R. Lenz used the "Petrarch" parable for his relationship to Cornelia Goethe. Laura as a pseudonym for Josephine and as the name for her daughter, born in 1811, is indicative of the hidden meaning behind the requested drawing.